Influence of Private Extension Services on Practices and Perceptions of Shrimp Farmers (Indian Journal of Extension Education, 2025)
The study conducted in 2025 (January to April) to evaluate the perceptions of shrimp farmers regarding private extension services, focusing on quality, accessibility, cost, and impact on farming practices in Tamil Nadu, India. A sample of 150 shrimp farmers was selected using proportionate random sampling from five districts; Nagapattinam, Thanjavur, Thiruvarur, Cuddalore, and Ramanathapuram. Data were collected through a structured interview schedule and was analysed using SPSS software. The findings revealed that shrimp farmers generally held positive views of private extension services, particularly regarding updated market information (51%), addressing the needs of small and marginal shrimp farmers (50%), regular visits by extension agents (45%), and technical expertise (49%). However, challenges like geographical barriers (85%), lack of awareness (76%), and high service costs (59%). Among 17 variables, 10 were found to be significantly associated with shrimp farmers’ perception levels. Multiple regression analysis revealed that independent factors accounted for 64.7 per cent of the variation in farmers’ perceptions. The study suggests enhancing private extension services by addressing affordability and improving collaboration between the public and private sectors to improve shrimp farming productivity and income.